PENGARUH SENSITIVITAS HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUSU KENTAL MANIS : SEBUAH STUDI LITERATUR - Mat Ropik (Universitas Sarjanawiyata Tamansiswa, 2026)
The sweetened condensed milk (SCM) industry in Indonesia represents a strategic commodity sector with extensive market penetration, yet it faces the challenge of increasingly intense competition and market saturation. This study aims to provide a comprehensive synthesis of literature to map the most dominant factors influencing market behavior and consumer purchase decisions. The methodology employed is a Narrative Literature Review, integrating data from reputable databases such as Google Scholar and ScienceDirect. The analysis focuses on studies published within the last decade, utilizing content analysis and comparative methods. Findings indicate that price sensitivity acts as the primary evaluative variable for lower-middle consumer segments, given that SCM is perceived as a staple product with high price elasticity of demand. Meanwhile, promotional strategies serve as tactical stimulants capable of swiftly intervening in the decision-making process. These strategies often trigger brand switching and impulsive buying through short-term incentives that effectively bypass the consumer's rational evaluation system. This suggests that purchasing decisions in this commodity category are frequently reactive responses to prominent economic incentives at the point of sale, rather than the result of long-term planning. The implications of this research highlight the necessity for optimal price calibration and aggressive retail promotional strategies for industry practitioners to maintain sales volume. Furthermore, this study identifies a significant literature gap regarding the impact of digital promotion and social media algorithms, which requires further exploration within the context of the modern marketing ecosystem.